The big ugly monster and the little stone rabbit - Wormell, Christopher (UK : Red Fox, 2005)
A monster who is shunned for his ugliness finds relief from loneliness when he befriends an inanimate rabbit he carved from stone.
K-3.
K-3
English
Keywords: Friendship -- Juvenile fiction; Loneliness -- Juvenile fiction; Monsters -- Juvenile fiction; Rabbits -- Juvenile fiction; Statues -- Juvenile fiction; Chinese language materials; Friendship -- Fiction; Loneliness -- Fiction; Monsters -- Fiction; Rabbits -- Fiction; Statues -- Fiction; Chinese language; Friendship -- Fiction; Loneliness -- Fiction; Monsters -- Fiction; Rabbits -- Fiction; Sculpture -- Fiction